Impact of COVID-19 pandemic on the oncologic care continuum: urgent need to restore patients care to pre-COVID-19 era. (19th April 2023) - Osei, Ernest; Francis, Ruth; Mohamed, Ayan; Sheraz, Lyba; Soltani-Mayvan, Fariba
Abstract: Background: Globally, cancer is the second leading cause of death, and it is estimated that over 18·1 million new cases are diagnosed annually. The COVID-19 pandemic has significantly impacted almost every aspect of the provision and management of cancer care worldwide. The time-critical nature of COVID-19 diagnosis and the large number of patients requiring hospitalisation necessitated the rerouting of already limited resources available for cancer services and programmes to the care of COVID-19 patients. Furthermore, the stringent social distancing, restricted in-hospital visits and lockdown measures instituted by various governments resulted in the disruption of the oncologic continuum including screening, diagnostic and prevention programmes, treatments and follow-up services as well as research and clinical trial programmes. Materials and Methods: We searched several databases from October 2020 to January 2021 for relevant studies published in English between 2020 and 2021 and reporting on the impact of COVID-19 on the cancer care continuum. This narrative review paper describes the impact of the COVID-19 pandemic on the cancer patient care continuum from screening and prevention to treatments and ongoing management of patients. Conclusions: The COVID-19 pandemic has profoundly impacted cancer care and the management of cancer services and patients. Nevertheless, the oncology healthcare communities worldwide have done phenomenal work with joint and collaborative efforts, utilising best available evidence-based guidelines to continue to give safe and effective treatments for cancer patients while maintaining the safety of patients, healthcare professionals and the general population. Nevertheless, several healthcare centres are now faced with significant challenges with the management of the backlog of screening, diagnosis and treatment cases. It is imperative that governments, leaders of healthcare centres and healthcare professionals take all necessary actions and policies focused on minimising further system-level delays to cancer screening, diagnosis, treatment initiation and clearing of all backlogs cases from the COVID-19 pandemic in order to mitigate the negative impact on cancer outcomes.